Ergonomically Based Garbage Transport Trolley Design Based on Anthropometric Data - Sari, Resy Kumala; Tabagus, Raka; Nur, Muhammad; Chen, Yi-Lang (Journal of Engineering Science and Technology Management (JES-TM), 2023)
The aims of this research are: 1. Able to design and build functional and ergonomic trolleys based on anthropometric data. 2. Able to demonstrate the efficiency of physical products from trolleys to material handling aspects. 3. To make products that can facilitate the transportation of waste to temporary waste disposal sites (TPS).Data collection was carried out by conducting interviews and measuring the body dimensions to 20 respondents consisting of 10 industrial engineering students class of 2018 and 10 random respondents aged 22-57 years. For the design of the trolley, there are 4 data variables that will be used, namely LB (44 cm), TPB (101.90 cm), JTD (63.10), PTT (16 cm) and several additional parts to make it more ergonomic and efficient. The conclusions of this study are 1. The design and manufacture of the trolley is in accordance with the anthropometric size of the human body where the trolley is very functional by providing a pulley on the trolley so as to facilitate the process of moving to the four temporary garbage disposals (TPS) and providing 3-axis wheels which function to facilitate the collection of waste through the stairs. Thus reducing complaints of diseases such as injuries to muscles, tendons, ligaments, nerves, cartilage, bones, or blood vessels in the hands, feet, neck, and back. 2. The physical product of the trolley is in accordance with anthropometric aspects and the trolley is also more efficient in its use.